Association of Single Nucleotide Polymorphisms from Angiogenesis-Related Genes, ANGPT2, TLR2 and TLR9, with Spontaneous Preterm Labor - Wujcicka, Wioletta Izabela; Kacerovsky, Marian; Krygier, Adrian; Krekora, Michał; Kaczmarek, Piotr; Grzesiak, Mariusz (Current issues in molecular biology, 2022)
In this study, we hypothesized that the changes localized at angiopoietin-2 (ANGPT2), granulocyte-macrophage colony-stimulating factor (CSF2), fms-related tyrosine kinase 1 (FLT1) and toll-like receptor (TLR) 2, TLR6 and TLR9 genes were associated with spontaneous preterm labor (PTL), as well as with possible genetic alterations on PTL-related coagulation. This case-control genetic association study aimed to identify single nucleotide polymorphisms (SNPs) for the aforementioned genes, which are correlated with genetic risk or protection against PTL in Polish women. The study was conducted in 320 patients treated between 2016 and 2020, including 160 women with PTL and 160 term controls in labor. We found that ANGPT2 rs3020221 AA homozygotes were significantly less common in PTL cases than in controls, especially after adjusting for activated partial thromboplastin time (APTT) and platelet (PLT) parameters. TC heterozygotes for TLR2 rs3804099 were associated with PTL after correcting for anemia, vaginal bleeding, and history of threatened miscarriage or PTL. TC and CC genotypes in TLR9 rs187084 were significantly less common in women with PTL, compared to the controls, after adjusting for bleeding and gestational diabetes. For the first time, it was shown that three polymorphisms-ANGPT2 rs3020221, TLR2 rs3804099 and TLR9 rs187084 -were significantly associated with PTL, adjusted by pregnancy development influencing factors.
Keywords: angiogenesis; genotyping; spontaneous preterm labor; pregnancy; restriction fragment length polymorphism; single nucleotide polymorphism